SEEING MAXIM VIOLATION IN EFL CLASSROOM INTERACTION - Mohammad Soni; Sinta Dewi; Sulistia Alawiah (Institut Pendidikan Indonesia Garut, 2022)
In relating with other people, the cooperative principle may be done to make a dialogue run well and efficiently. However, there are chances when speakers have to violate a maxim because of some reason. This study aims to determine the kinds of maxim violations done by the students during classroom interaction and the reasons behind the students violating the maxims. This study used observation and interview methods to collect the data. The study results show that there are three maxims violated by students, namely violating the maxim of quantity, relevance, and quality, with a total of 25 utterances. The students violate the maxim because they want to save face and build someoneâ€™s belief.Â